Evaluation of Direct Oral Anticoagulation Therapy in Heart and Lung Transplant Recipients. (September 2016) - Lichvar, Alicia B.; Moore, Cody A.; Ensor, Christopher R.; McDyer, John F.; Teuteberg, Jeffrey J.; Shullo, Michael A.
Context: Anticoagulation therapy is common in thoracic transplant recipients. Direct oral anticoagulants (DOACs) are alternatives to warfarin therapy, but characterization of their use in solid organ transplant is absent. Objective: The primary objective of this study was to describe a thoracic transplant patient population initiated on DOAC therapy. Secondary objectives were to assess adverse reactions, venous thromboembolism (VTE) recurrence, and drug–drug interactions during DOAC therapy. Study Design: Single-center retrospective cohort study. Setting: A tertiary care medical center including inpatient hospitalization and outpatient transplant clinic visits. Patients: Thoracic transplant recipients who were initiated on DOACs between May 1, 2011, and March 1, 2015, at the University of Pittsburgh Medical Center were included. Results: A total of 37 patients were included in the analysis. A majority of the patients were lung transplant recipients (86.4%) with a median age of 60.7 years. Twenty-eight patients had a history of VTE. The primary indication for DOAC initiation was VTE (86.5%). Rivaroxaban (78.4%) was the most commonly utilized agent. Dose reductions for major drug interactions (37.8%), renal insufficiency (10.8%), or both (8.1%) occurred within the study. Two patients had breakthrough VTE during DOAC therapy. Eight bleeding events were reported in the cohort, one of which was considered a major bleed. There was no difference in the incidence of bleeding in patients with drug–drug interactions and without drug–drug interactions during DOAC therapy (26.0% vs 7.1%, P = .154). Conclusion: Direct oral anticoagulant therapy was well tolerated by thoracic transplant recipients. Drug interactions and renal dose adjustments were common.